Bamboo biochar and carbonation enhanced the compressive and flexural strength of cement mortar - Chin, Siew Choo; Pravina K., Gunasekaran; Che, Jialing; Anand, N.; Jolius, Gimbun (Elsevier Ltd, 2025)
The construction industry faces growing pressure to adopt sustainable materials that enhance both structural performance and environmental benefits. This study investigates the potential of bamboo biochar as a sustainable filler to strengthen cement mortar while contributing to CO₂ sequestration. The primary objective is to evaluate the effects of bamboo biochar addition, alongside carbonation treatment, on the mechanical properties of cement mortar. The surface morphology of the biochar was characterized using scanning electron microscopy, while mortar mixes with varying water-to-cement (w/c) ratios (0.45–0.55) and biochar dosages (2 %–8 %) were prepared. Flowability, compressive, and flexural strength tests were conducted on samples cured for 7–56 days, with a control mix for comparison. Results revealed that a 6 % biochar addition with a w/c ratio of 0.45 yielded optimal performance, achieving compressive and flexural strengths of 46.98 MPa and 9.60 MPa, respectively. Carbonation further enhanced these strengths by up to 24 % and 9 %, while biochar incorporation increased CO₂ sequestration by 53 % compared to the control. These findings demonstrate that bamboo biochar not only improves mechanical strength through mechanisms such as internal curing, filler effect, nucleation, and improved interfacial bonding but also contributes to carbon capture. This dual benefit underscores its significance as a promising material for sustainable and resilient construction practices.